Madrasah Committee: Implementation of â€œMerdeka Belajarâ€ â€Žand The Progress of Islamic Education in Pamekasan - M. Sahibuddin; Supandi; Untung; Akhmadul Faruq (TADRIS: Jurnal Pendidikan Islam, 2024)
The madrasa committee is an independent institution formed by educational institutions to have a role in improving the quality and services of education in the form of direction, support for both educational facilities and infrastructure, and supervision of the implementation of education in each education unit. The madrasa committee plays a role as an Education Advisory, Education Supporting, Education Mediatory, and even controlling the implementation of Education itself. We must carry out the policy of "Merdeka Belajar", because this is a mandate from the government that all education practitioners in each education unit are required to implement "Merdeka Belajar" policy which is then poured into the "Guru Penggerak", the education practitioners are through the program in each education unit. Therefore, madrasa committees must be present and support the policies of this program. In this research method, the researcher used a qualitative approach with a phenomenological descriptive type. The informants in this study are those who the researchers consider to know and are related to this research. The results of the study show that: 1) Madrasah committees have the duty and responsibility to make madrasas a progressive educational institution, 2) The potential and strengths of madrasas must be able to be explored and maximized so that later madrasas are no longer the number 2 educational institution but have become the leading choice of the community, 3) Madrasas become centers of excellence for education because educational institutions in the form of madrasas present more menus and scientific variants when compared to educational institutions in the form of schools.